The insights of pet cokes/palm kernel shell activated carbon as CO2 adsorbent: equilibrium, kinetics, thermodynamics, and regeneration performance - Rashidi, N.A. (John Wiley and Sons Ltd, 2022)
BACKGROUND: Over the years, activated carbon has been widely used for environmental applications, including liquid or gas phase applications. However, there are many hurdles for researchers in the activated carbon field to overcome when it comes to non-renewable materials, the utilization of individual precursors, and the complex multistep procedures of activated carbon synthesis. Therefore, in this study, the facile mechanochemical potassium carbonate (K2CO3) activation of blended precursors â palm kernel shell and petroleum coke â was investigated in terms of the activated carbon yield and carbon dioxide (CO2) adsorption capacity. RESULTS: The optimum configuration of the activated carbon production was found at temperature of 680Â°C, holding time of 60 min, and impregnation ratio of 1.75:1. The CO2 adsorption data at 25â120Â°C was best represented by the Sips model with R2Â > 0.9999, where maximum CO2 adsorption capacity (qmax) was within the range of 2.24â4.32 mmol/g. The kinetic analysis was well-represented by the pseudo-second order model due to the high R2 and low sum of square of errors (ERRSQ) value. In terms of thermodynamic analysis, it showed that the CO2 adsorption process was physical, exothermic, and spontaneous at lower temperature. CONCLUSION: Overall, the integration of agricultural and industrial waste to value-added activated carbon was feasible not only in reducing waste disposal problems but also in facilitating CO2 mitigation. Â© 2022 Society of Chemical Industry (SCI). Â© 2022 Society of Chemical Industry (SCI).